Effect of adding at-bak probiotics with different concentrations in feed on absolute weight growth of whiteleg shrimp (Litopenaeus vannamei) DOC 30 - Prestisia Purnama Dewanti; Sumaryam Sumaryam; Didik Budiyanto (Universitas Teuku Umar, 2026)
Whiteleg shrimp (Litopenaeus vannamei) is one of the national superior commodities that contribute 40% to the Indonesian fishing industry. Feeding through the addition of external additives, namely probiotics, will increase whiteleg shrimp production so as to meet foreign market demand. One of the probiotic products in shrimp farming is the trademark “AT-Bak” which contains Lactobacillus plantarum, Lactobacillus fermentum, Bacillus subtilis and Pseudomonas putida. The purpose of the study was to determine the effect of the addition of probiotics with different concentrations in the feed on the absolute weight growth of whiteleg shrimp (Litopenaeus vannamei) DOC 30. The method used in this study was an experimental method. The design used is an experimental method, using a completely randomized design (CRD) with 4 treatments and 6 replicates. The treatment given was the provision of probiotics with concentrations: treatment A (15 ml/kg feed); B (20 ml/kg feed); C (25 ml/kg feed); D (30 ml/kg feed). The results showed that the provision of probiotics with different concentrations had a significant effect on the absolute weight growth of whiteleg shrimp (Litopenaeus vannamei) DOC 30. Treatment D with a concentration of 30 ml/kg gave the highest absolute weight growth of 9.37 g. Water quality data during the study obtained water temperature ranged from 27.9 to 30˚C, salinity ranged from 28 to 32 ppt, pH ranged from 7.8 to 8.4, and oxygen range from 4.7 to 5 mg/l.